2012
DOI: 10.2106/jbjs.k.00444
|View full text |Cite
|
Sign up to set email alerts
|

Two to Twenty-Year Survivorship of the Hip in 810 Patients with Operatively Treated Acetabular Fractures

Abstract: Open reduction and internal fixation of displaced acetabular fractures was able to successfully prevent the need for subsequent total hip arthroplasty within twenty years in 79% of the patients. The results represent benchmark comparative data for any future and past studies on the outcome of surgical fixation of acetabular fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

17
255
8
9

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 343 publications
(289 citation statements)
references
References 13 publications
17
255
8
9
Order By: Relevance
“…We evaluated the baseline data in the 2 groups and noted a larger degree of preoperative dislocation of the acetabular roof in the 3D group, and similar distribution between the 2 groups with respect to fracture type, age, and sex. The baseline parameters were comparable to those in the other acetabular fracture studies reported in this manuscript (Briffa et al 2011, Oberst et al 2012, Tannast et al 2012, Shazar et al 2014). Propensity score methods are an option to reduce potential bias between trial arms in non-randomized trials.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…We evaluated the baseline data in the 2 groups and noted a larger degree of preoperative dislocation of the acetabular roof in the 3D group, and similar distribution between the 2 groups with respect to fracture type, age, and sex. The baseline parameters were comparable to those in the other acetabular fracture studies reported in this manuscript (Briffa et al 2011, Oberst et al 2012, Tannast et al 2012, Shazar et al 2014). Propensity score methods are an option to reduce potential bias between trial arms in non-randomized trials.…”
Section: Discussionsupporting
confidence: 81%
“…The strong correlation between the quality of articular reduction of the weight-bearing dome and the clinical outcome after 1–2 years (Giannoudis et al 2005, Tannast et al 2012) suggests that the residual steps and gaps that remain undetected with the fluoroscope—but are identifiable with 3D imaging—have clinical relevance and should be corrected.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In der Serie von Matta zeigte sich, dass nach 2-20 Jahren in 21% eine Hüfttotalprothe-se nötig wurde [28]. Risikofaktoren für ein schlechtes Resultat sind das Frakturmuster, die superomediale Acetabulumdomimpaktion, das initiale Ausmaß der Frakturdislokation, der Femurkopfschaden, das erhöhte Patientenalter, die verzögerte operative Versorgung und v. a. die Qualität der Reposition [1,2,7,28]. Frakturen mit der Hauptdislokation im vorderen Pfeiler werden über anteriore Zugänge versorgt.…”
unclassified